2021
DOI: 10.1007/s00455-021-10357-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Remote Examination of Deglutition Based on Consensus Surveys of Clinicians (Part I): Selection of Examination Items

Abstract: In order to ensure appropriateness and feasibility of examination items for remote evaluation for deglutition disorders, a questionnaire based on the Delphi method was administered to 122 speech–language–hearing therapists (STs), and a set of examination items was selected. The participants were instructed to view a video recording of a remote assessment situation and answer a 30-item questionnaire. Of 19 items ensuring the appropriateness for deglutition disorders detection, 13 items ultimately met the consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In the questionnaire surveys of SLHTs in Part I of our study, the most common comments were "concerns about the quality and stability of the voice that may be heard through the device. [ 22 ]" However, there was also a high level of agreement in the items that included assessment of voice quality: "sustained phonation and voice quality," "water intake (3 ml, 10 ml)," and "staple food intake (pharyngeal response)." Ward et al [ 16 ] found a high degree of agreement between remote and face-to-face comparisons in their evaluation of wet voice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the questionnaire surveys of SLHTs in Part I of our study, the most common comments were "concerns about the quality and stability of the voice that may be heard through the device. [ 22 ]" However, there was also a high level of agreement in the items that included assessment of voice quality: "sustained phonation and voice quality," "water intake (3 ml, 10 ml)," and "staple food intake (pharyngeal response)." Ward et al [ 16 ] found a high degree of agreement between remote and face-to-face comparisons in their evaluation of wet voice.…”
Section: Discussionmentioning
confidence: 99%
“…There are two major differences between RED and other existing tests. First, RED consists only of items that were judged to be remotely feasible in our Part I study [ 22 ]. In contrast, other standardized tests developed for face-to-face conditions have been directly adapted for remote evaluation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations